Pengaruh Kompetensi Manajerial Kepala Sekolah, Motivasi Berprestasi, dan Pemanfaatan Aplikasi Ruang GTK Terhadap Kompetensi Profesional Guru Sekolah Dasar di Kecamatan Japah Kabupaten Blora - Marsih Marsih; Bunyamin Bunyamin; Muhammad Prayito (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study was motivated by the low level of professional competence among elementary school teachers in Japah District, Blora Regency, which is presumed to be influenced by the managerial competence of school principals, achievement motivation, and the utilization of the Ruang GTK application. The purpose of this study was to analyze the influence of these variables, both partially and simultaneously, on teachers’ professional competence. This research employed a quantitative correlational approach with an ex post facto design. The population consisted of 191 elementary school teachers, with a sample of 129 teachers selected through a sampling technique. Data were collected using questionnaires and analyzed using simple and multiple regression. The results indicate that: (1) the managerial competence of school principals has a significant effect on teachers’ professional competence (48.0%); (2) achievement motivation has a significant effect (60.0%); (3) the utilization of the Ruang GTK application has a significant effect (60.5%); and (4) simultaneously, these variables have a significant effect with a combined contribution of 66.1%. These findings suggest that improving teachers’ professional competence is strongly influenced by leadership quality, internal motivation, and the effective use of educational technology. Therefore, efforts to enhance teacher competence should focus on strengthening principals’ managerial skills, fostering teachers’ achievement motivation, and optimizing the use of digital learning platforms to support more effective and engaging instruction.